2009
DOI: 10.1128/aem.02869-08
|View full text |Cite
|
Sign up to set email alerts
|

Maternally and Naturally Acquired Antibodies to Shiga Toxins in a Cohort of Calves Shedding Shiga-Toxigenic Escherichia coli

Abstract: Calves become infected with Shiga toxin-producing Escherichia coli (STEC) early in life, which frequently results in long-term shedding of the zoonotic pathogen. Little is known about the animals' immunological status at the time of infection. We assessed the quantity and dynamics of maternal and acquired antibodies to Shiga toxins (Stx1 and Stx2), the principal STEC virulence factors, in a cohort of 27 calves. Fecal and serum samples were taken repeatedly from birth until the 24th week of age. Sera, milk, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…The observation that three of four STEC per genoserotypes possess predominantly stx 1 (O26:H11, O156:H25, O182:H25), while STEC spo genoserotypes are significantly more often positive for stx 2 is consistent with the observation that calves are first colonized by an STEC-1 population, which is later expanded by the occurrence of STEC-2 isolates (16,35,61), implying that stx 1 -positive E. coli are particularly adopted to be part of the normal microbiota in the bovine host. Even though only four cattle herds were sampled, albeit intensively, we detected 4 (O26, O103, O145, O157) of the 5 (additionally O111) EHEC O antigens, which define strains that account for most of the human HUS cases in Germany (31,62,63).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The observation that three of four STEC per genoserotypes possess predominantly stx 1 (O26:H11, O156:H25, O182:H25), while STEC spo genoserotypes are significantly more often positive for stx 2 is consistent with the observation that calves are first colonized by an STEC-1 population, which is later expanded by the occurrence of STEC-2 isolates (16,35,61), implying that stx 1 -positive E. coli are particularly adopted to be part of the normal microbiota in the bovine host. Even though only four cattle herds were sampled, albeit intensively, we detected 4 (O26, O103, O145, O157) of the 5 (additionally O111) EHEC O antigens, which define strains that account for most of the human HUS cases in Germany (31,62,63).…”
Section: Resultssupporting
confidence: 75%
“…Clones suspected to have been shed by a single animal or circulating within a herd for at least 4 months were defined as persistent colonization type (STEC per ), whereas isolates detected either Յ2 months (two successive sampling time points) and/or occasionally with at least a 4-month gap in detection were considered sporadically occurring (STEC spo ), resulting in 77 STEC per and 85 STEC spo isolates. Additionally, 16 isolates obtained from calves during a 6-month monitoring study (35) were used as unrelated controls, resulting in a total of 178 STEC isolates in the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calves bearing maternal and acquired antibodies against Stx1 and in lesser extent, Stx2 [64] have been reported, sometimes with high frequency of reacting animals [65]. These antibodies have also been detected in natural bovine colostra [66] and in cows immunized with Stx2 [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Both natural and experimental EHEC infections have shown that cattle develop serum antibodies against intimin, EspA, EspB, and Tir and the Shiga toxins Stx1 and Stx2 (5-7), although the latter are poorly immunogenic in cattle (8). Intimin, EspA, and EspB are more immunogenic in ruminants since oral infection of sheep with a Shiga toxin-negative O157:H7 E. coli strain induced antibody responses against intimin, EspA, and EspB (9).…”
mentioning
confidence: 99%